RIGHT TO EDUCATION IN INDIA - Akash Trikha, Nilanjan Chakraborty (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current research paper talk about the free and compulsory education is provided for children in India. It begins by discussing the 86th Amendment to India’s Constitution, which termed the right to education as a fundamental right granted by India’s Constitution and how India requires mandatory education rather than compulsory education. The paper further talks about the right to education with respect to the Constitution of India and how it was always envisioned to make the right a Fundamental Right but due to financial limitations, the same could not be achieved at the time the Constitution was framed. The paper then discusses some of the salient features of the Right of Children to Free and Compulsory Education Act, 2009 before it concludes with discussing the need of the children and parents to be made aware of the existence of such right